Optimasi SIKS-Ng di Dinas Sosial Provinsi Sulawesi Tengah - Gaghauna, Vanessa Gloria; Mujib Safar, Muhammad; Wahab, Abdul (Jurnal Indonesia Sosial Sains, 2022)
The purpose of this study is to find out the extent of the optimal implementation of the SIKS-NG application in the Social Service of Central Sulawesi Province. This research is descriptive and uses a qualitative approach. The results showed that the facilities and infrastructure and flexibility of the workspace and the amount of human resources (HR) are still inadequate so that it needs to be optimized so that the use of the SIKS-NG application can run optimally.